(untitled) (Journal of Engineering, 2011)
The investigation included PHE performance variation with heat exchanger dimensions, plate spacing, inlet air velocities and inlet air temperatures. The momentum and energy equations were solved in 3-dimensions by using FLUENT 5.3 software and heat exchanger performance parameters were extracted from the post processing of the numerical data. In addition, a 2-dimensional fluid flow and heat transfer numerical analysis for the crossflow PHE was carried out. A numerical code based on the finite difference method and the SIMPLE algorithm was developed to solve the governing equations. The result of the numerical study for PHE performance shows that for both air streams the maximum thermal gradient occurs at 0.5 m/s inlet air velocity while the minimum occurs at 5 m/s velocity. Furthermore; the greater thermal gradient for the both air streams occurs at 3 mm plate spacing and decrease progressively to the lowest gradient at 10 mm spacing. Also, the results indicated that indirect evaporative cooling could be applied to obtain suitable outlet air temperatures for low and medium values of wet-bulb temperatures in arid climates.